How quality of work-life affects work-life balance at Lablink (M) Sdn Bhd / Sharifah Amalina Syed Hud and Intan Juzailah Ramli - Syed Hud, Sharifah Amalina; Ramli, Intan Juzailah (Faculty of Business and Management, 2016)
Quality of work-life in terms of compensation and benefits policy, work hour duration, and work facilities provided by company are among the factor that influence work-life balance. Although, there is increasing awareness of the importance of work-life balance towards employee, there are some employers who are failed to implement work-life balance in work environment. There are also raising concerns of Karoshi effect towards Malaysian job environment. Therefore, this study is trying to identify the relationship among compensation and benefits policy, work hour, and work facilities with employee work-life balance as well as to indicate the most influential factor among the three factors. The study takes place at Lablink (M) Sdn. Bhd. About 85 questionnaires were distributed to employees randomly from the total population of 95 employees. The sample was identified using convenient sampling techniques. The correlation of the variables was compute using SPSS 20.0 DATA software analysis. This study implies that the work hour is the main factors that influence work-life balance at Lablink (M) Sdn. Bhd. However, based on previous study, Compensation and Benefit Policy and Work Facilities are among the factors that influence Work-life Balance (Saklani, 1979). In conclusion, there is improvement needed to ensure employee able to achieve work-life balance.